Rapid label-free detection of E. coli using antimicrobial peptide assisted impedance spectroscopy. Issue 23 (3rd September 2015) - Jiang, Keren; Etayash, Hashem; Azmi, Sarfuddin; Naicker, Selvaraj; Hassanpourfard, Mahtab; Shaibani, Parmiss Mojir; Thakur, Garima; Kaur, Kamaljit; Thundat, Thomas
Abstract : A compact, label-free sensor array for rapid detection of Escherichia coli ( E. coli ) using antimicrobial peptide assisted impedimetric sensor platform. Abstract : There is an increasing demand for rapid detection of waterborne pathogens to monitor drinking water safety. We demonstrate a compact, label-free sensor array for rapid detection of Escherichia coli ( E. coli ) in contaminated water samples using antimicrobial peptide assisted impedimetric sensor platform. Interdigitated electrode arrays immobilized with the antimicrobial peptide Colicin V (ColV) were used to screen the affinity towards different bacterial strains by monitoring impedance variations in real-time. This ColV assisted impedance biosensor exhibited high selectivity towards Gram-negative strains particularly towards E. coli strains. This selective detection of E. coli from other strains was observed at 10 2 cfu mL −1, which is clinically relevant. The sensor can detect E. coli from 10 2 to 10 6 cfu mL −1 in water sample at pH 7 to 9. These results show that the antimicrobial peptide ColV assisted impedimetric array is capable of rapid, specific detection of E. coli in contaminated water samples.